2022
DOI: 10.1002/slct.202203307
|View full text |Cite
|
Sign up to set email alerts
|

Design of Dual Purpose Fe‐metallogel for Magnetic Refrigeration and Fabrication of Schottky Barrier Diode

Abstract: The impetus for the present work was to design multifunctional inorganic materials that can be utilized in their original assynthesized state of the matter. Accordingly, we have successfully designed a benzene-tricarboxylic acid based dual-purpose Fe-metallogel that can be used as an efficient material for cryogenic magnetic cooling as well as electronic device fabrication as Schottky barrier diode in their original gel state. The metallogel shows remarkable mechanical strength, selfsustainability and thixotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Saha et al prepared Fe-1,2,4-BTC MOG by mixing 1,2,4-benzenetricarboxylic acid and Fe 3+ in DMF. 125 FESEM showed that the fresh gel has a fiber network structure, 20–25 nm in diameter, but SEM and TEM showed that the xerogel consists of deformed nanoparticles. The nonlinear curvature was revealed by the I – V plot of the MS junction-based gel thin film device with a rectification ratio of 42.19 at ±1 V. The conductivity of the device in the linear region was about 4.53 × 10 −6 S m −1 .…”
Section: Metal–organic Gels As Conductive Materialsmentioning
confidence: 99%
“…Saha et al prepared Fe-1,2,4-BTC MOG by mixing 1,2,4-benzenetricarboxylic acid and Fe 3+ in DMF. 125 FESEM showed that the fresh gel has a fiber network structure, 20–25 nm in diameter, but SEM and TEM showed that the xerogel consists of deformed nanoparticles. The nonlinear curvature was revealed by the I – V plot of the MS junction-based gel thin film device with a rectification ratio of 42.19 at ±1 V. The conductivity of the device in the linear region was about 4.53 × 10 −6 S m −1 .…”
Section: Metal–organic Gels As Conductive Materialsmentioning
confidence: 99%
“…The arrangement of the molecular interaction between the gelator molecules and entrapped solvents gets perturbed by such external stimuli, and significant changes in the associated properties of the soft materials can be observed and exploited. Various noncovalent interactions such as van der Waals, hydrophobic, dipole–dipole, and H-bonding interactions play defining roles in tuning the structures. Although the organic gelator molecules can form organogels, the incorporation of metal ions inside them can impart some additional features to make metallogels suitable for various applications such as dye adsorption, biomaterials, catalysis, drug delivery, , material science, sensing, antimicrobial activity, artificial light-harvesting systems, semiconducting devices, and many others. , It is also worth mentioning that in some cases, the insertion of metal in an organic system can make it prone to gel formation due to the additional force of interactions between the organic entity and metal atoms/ions (Figure ). When employing the metallogels for different functionalities, one of the crucial factors is the gel strength.…”
Section: Introductionmentioning
confidence: 99%
“…hydrogen bonding interaction, van der Waals forces, dipole–dipole, charge transfer, π–π stacking, etc., are established in literature. Integration of metal ion with the gelators proposes a noteworthy platform to functionalize soft materials with added superior beneficial functionalities . Few celebrated practical applications of gels such as nonlinear optics, , artificial light-harvesting systems, , molecular sensing, , biomedical applications, drug delivery, tissue engineering, , cell imaging, antibacterial and antifungal activity, 3D printing, magnetism, , catalysis, , electronics, light emitting diodes, biotechnology, , etc. are recognized in the scientific domain.…”
Section: Introductionmentioning
confidence: 99%